2006
DOI: 10.4314/ajtcam.v3i4.31174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of standardised herbal extracts in type 1 diabetes - an experimental study

Abstract: In the present study, the hypoglycemic activity of Withania somnifera Dunal, Allium sativum Linn., Gymnema sylvestre (Retz.) Schult, Ferula foetida (Bunge.) Reg. and Murraya koenigii (L.) Spreng. extracts have been studied in an experimental model of type 1 diabetes. Type 1 diabetes was induced in albino rats by a single intraperitoneal injection of streptozotocin (60 mg/kg). Rats with fasting blood glucose (FBG) more than 250 mg/dl, 72 h after STZ administration, were treated with extracts of above mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Diabetes was induced by a single intraperitoneal injection of streptozotocin to animals fasted overnight at a dose of 60 mg/kg body weight in a volume of 0.5 ml saline [11]. Blood samples were obtained from the retro-orbital plexus in streptozotocin-injected animals after 72 h following an overnight fast.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Diabetes was induced by a single intraperitoneal injection of streptozotocin to animals fasted overnight at a dose of 60 mg/kg body weight in a volume of 0.5 ml saline [11]. Blood samples were obtained from the retro-orbital plexus in streptozotocin-injected animals after 72 h following an overnight fast.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Figure , PRISMA flow‐chart of study selection, depicts the overall process of study selection. A total of 24 studies met the inclusion criteria; in‐vitro ( n = 6; Huerta, Mihalik, Becket, Maitin, & Vattem, ; Jonathan, Rivka, Avinoam, Lumír, & Nirit, ; Khan, Khan, & Ali, ; Nirupama, Devaki, Nirupama, & Yajurvedi, ; Shah, Khan, Vakil, & Qureshi, ; Singh, Joshi, & Jatwa, ); pre‐clinical ( n = 13 [mice model, n = 2; rat model, n = 11]; Anwer et al, ; Anwer, Sharma, Pillai, & Iqbal, ; Anwer, Sharma, Pillai, & Khan, ; Jain, Pandhi, Singh, & Malhotra, ; Kiasalari, Khalili, & Aghaei, ; Kyathanahalli, Manjunath, & Muralidhara, ; M. S. Parihar, Chaudhary, Shetty, & Hemnani, ; P. Parihar, Shetty, Ghafourifar, & Parihar, ; Sarangi, Jena, Sarangi, & Swain, ; Tekula, Khurana, Anchi, & Godugu, ; Thakur, Dey, Shyam Chatterjee, & Kumar, ; Udayakumar et al, , ); clinical ( n = 5; Agnihotri, Sontakke, Thawani, Saoji, & Goswami, ; Andallu & Radhika, ; Nayak, Nayak, Panda, & Das, ; Usharani, Fatima, Kumar, & Kishan, ; Usharani, Kishan, Fatima, & Kumar, ). The duration of included pre‐clinical studies ranged from 10 to 56 days, and clinical trials from 30 to 84 days which used authenticated extract of W. somnifera .…”
Section: Resultsmentioning
confidence: 99%
“…To the facts, this is the first systematic review and meta‐analysis evaluating the efficacy/effectiveness, safety and tolerability of W. somnifera treatment in DM. Of 13 pre‐clinical studies, four studies investigated effect of W. somnifera in type‐2 diabetes rats (Anwer et al, , , ; Thakur et al, ), three studies in type‐1 diabetes rats (Jain et al, ; Kiasalari et al, ; Tekula et al, ) and the remaining studies did not mention about the type of diabetes condition (Kyathanahalli et al, ; M. S. Parihar et al, ; P. Parihar et al, ; Sarangi et al, ; Udayakumar et al, , ). However, by virtue of their pancreatic β‐cell reduction/toxicity by AM/STZ, these studies mimicked either type‐1 or type‐2 diabetes or both conditions (Durg, Veerapur, Neelima, & Dhadde, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that insulin is unable to completely inhibit protein glycation which can maintain increased oxidative stress in diabetic tissues. These problems led several investigators to focus their attention on the traditional medicines (Jain et al, 2006).…”
Section: Introductionmentioning
confidence: 99%